Comparison of 2 commercial turkey hybrids: productivity, occurrence of breast myopathies, and meat quality properties. (5th February 2019) - Zampiga, M; Tavaniello, S; Soglia, F; Petracci, M; Mazzoni, M; Maiorano, G; Meluzzi, A; Clavenzani, P; Sirri, F
ABSTRACT: This study was undertaken to compare productive performance, occurrence of breast myopathies, chemical composition, and technological properties of the meat in 2 dominant commercial turkey hybrids. A total of 972 1-day-old male turkey poults (equally divided in hybrid A and B) were randomly distributed in 18 floor pens. Overall, productive performance resulted similar between the genotypes, although they showed different growth profile (turkeys from group B grew up faster up to 84 d). Regarding the occurrence of myopathies, the percentage of breasts affected by white striping was markedly higher in both genotypes (46 vs. 60% of severe lesions, respectively for A and B; P < 0.05), while the occurrence of spaghetti meat-like condition was negligible. The histological features of the different categories of meat abnormalities resulted similar to those previously described for chicken hybrids. The technological traits such as ultimate pH, lightness, redness, marinade uptake, cooking losses, and shear force were not significantly affected by the genotype. However, turkeys from group B exhibited lower yellowness (b*, 0.50 vs. 1.04; P < 0.05) and higher drip losses (1.34 vs. 1.26%; P < 0.05). The shelf-life test on thigh meat showed no significant changes in meat color over the storage time in both hybrids, whereas thigh meat from group A showed absolute lower values of lightness (L*) and yellowness (b*) ( P < 0.05). Lipid oxidation of thigh meat significantly increased during storage, although no significant difference was found between the hybrids. Proximate composition and intramuscular collagen properties resulted similar between genetic lines with the exception of total fat content (1.55 vs. 1.21%, respectively for A and B; P < 0.05). The genotype had a moderate effect on fatty acid families of breast meat as only monounsaturated fatty acid content was significantly affected (31.7 vs. 29.8%, respectively for A and B). In conclusion, the overall productive traits of commercial turkeys, including the occurrence of muscle myopathies, as well as quality attributes of fresh and refrigerated meat were only slightly affected by the genotype.